Bradykinin postconditioning protects rat hippocampal neurons after restoration of spontaneous circulation following cardiac arrest via activation of the AMPK/mTOR signaling pathway - Shi-Rong Lin; Qing-Ming Lin; Yu-Jia Lin; Xin Qian; Xiao-Ping Wang; Zheng Gong; Feng Chen; Bin Song (Neural Regeneration Research, 2022)
Bradykinin (BK) is an active component of the kallikrein-kinin system that has been shown to have cardioprotective and neuroprotective effects. We previously showed that BK postconditioning strongly protects rat hippocampal neurons upon restoration of spontaneous circulation (ROSC) after cardiac arrest. However, the precise mechanism underlying this process remains poorly understood. In this study, we treated a rat model of ROSC after cardiac arrest (induced by asphyxiation) with 150 μg/kg BK via intraperitoneal injection 48 hours after ROSC following cardiac arrest. We found that BK postconditioning effectively promoted the recovery of rat neurological function after ROSC following cardiac arrest, increased the amount of autophagosomes in the hippocampal tissue, inhibited neuronal cell apoptosis, up-regulated the expression of autophagy-related proteins LC3 and NBR1 and down-regulated p62, inhibited the expression of the brain injury marker S100β and apoptosis-related protein caspase-3, and affected the expression of adenosine monophosphate-activated protein kinase/mechanistic target of rapamycin pathway-related proteins. Adenosine monophosphate-activated protein kinase inhibitor compound C clearly inhibited BK-mediated activation of autophagy in rats after ROSC following cardiac arrest, which aggravated the injury caused by ROSC. The mechanistic target of rapamycin inhibitor rapamycin enhanced the protective effects of BK by stimulating autophagy. Our findings suggest that BK postconditioning protects against injury caused by ROSC through activating the adenosine monophosphate-activated protein kinase/mechanistic target of the rapamycin pathway.